Solution‐Phase Crosstalk and Regulatory Interactions Between Multipotent Adult Progenitor Cells and Peripheral Blood Mononuclear Cells. (22nd October 2015) - Burrows, Gregory G.; van't Hof, Wouter; Reddy, Ashok P.; Wilmarth, Phillip A.; David, Larry L.; Raber, Amy; Bogaerts, Annelies; Timmerman, Lien; Pinxteren, Jef; Roobrouck, Valerie D.; Deans, Robert J.; Maziarz, Richard T.
Abstract : This study documents experiments quantifying solution‐phase cross talk between multipotent adult progenitor cells (MAPCs) and peripheral blood mononuclear cells. The potential impact of these studies includes development of a robust experimental framework to be used for preclinical evaluation of the specific mechanisms by which beneficial effects are obtained after treatment of patients with MAPCs. Abstract : Multipotent adult progenitor cells (MAPCs) are adult adherent stromal stem cells currently being assessed in clinical trials for acute graft versus host disease with demonstrated immunomodulatory capabilities and the potential to ameliorate detrimental autoimmune and inflammation‐related processes. Anti‐CD3/anti‐CD28 (3/28) activation of T cells within the peripheral blood mononuclear cell (PBMC) compartment was performed in the presence or absence of MAPCs. Liquid chromatography‐coupled tandem mass spectrometry was used to characterize the differential secretion of proteins, and transcriptional profiling was used to monitor mRNA expression changes in both cell populations. Overall, 239 secreted and/or ectodomain‐shed proteins were detected in the secretomes of PBMCs and MAPCs. In addition, 3/28 activation of PBMCs induced differential expression of 2, 925 genes, and 22% of these transcripts were differentially expressed on exposure to MAPCs in Transwell. MAPCs exposed to 3/28‐activated PBMCs showed differential expression of 1, 247 MAPC genes. Crosstalk was demonstrated by reciprocal transcriptional regulation. Secretome proteins and transcriptional signatures were used to predict molecular activities by which MAPCs could dampen local and systemic inflammatory responses. These data support the hypothesis that MAPCs block PBMC proliferation via cell cycle arrest coupled to metabolic stress in the form of tryptophan depletion, resulting in GCN2 kinase activation, downstream signaling, and inhibition of cyclin D1 translation. These data also provide a plausible explanation for the immune privilege reported with administration of donor MAPCs. Although most components of the major histocompatibility complex class II antigen presentation pathway were markedly transcriptionally upregulated, cell surface expression of human leukocyte antigen‐DR is minimal on MAPCs exposed to 3/28‐activated PBMCs. Significance: This study documents experiments quantifying solution‐phase crosstalk between multipotent adult progenitor cells (MAPCs) and peripheral blood mononuclear cells. The secretome and transcriptional changes quantified suggest mechanisms by which MAPCs are hypothesized to provide both local and systemic immunoregulation of inflammation. The potential impact of these studies includes development of a robust experimental framework to be used for preclinical evaluation of the specific mechanisms by which beneficial effects are obtained after treatment of patients with MAPCs.